2002
DOI: 10.1002/pros.10158
|View full text |Cite
|
Sign up to set email alerts
|

Response to a lethal dose of heat shock by a transient up‐regulation of clusterin expression followed by down‐regulation and apoptosis in prostate and bladder cancer cells

Abstract: Clusterin offers a protection to PC-3 and TSU-Prl cells against heat shock and plays an important role in the cascade of events initiated by heat shock. Prostate 53: 277-285, 2002.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…For example, oxidative stress of human diploid fibroblasts [22,35] or C 2 -ceramide-treatment of pancreatic cells [36] induced anti-proliferative responses and up-regulated clusterin/apoJ perhaps as an attempt to survive. In contrast, apoptotic stimuli such as UVB irradiation, dexamethasone-treatment [37], chemotherapeutic agents [23,38] or heat shock [39] induced apoptosis by markedly decreasing the expression of clusterin/ApoJ, in a dose-and time-dependent manner [23]. The downregulation of clusterin/apoJ in keratinocytes undergoing ropivacaine-mediated apoptosis is in agreement with previous studies [40].…”
Section: Discussionsupporting
confidence: 89%
“…For example, oxidative stress of human diploid fibroblasts [22,35] or C 2 -ceramide-treatment of pancreatic cells [36] induced anti-proliferative responses and up-regulated clusterin/apoJ perhaps as an attempt to survive. In contrast, apoptotic stimuli such as UVB irradiation, dexamethasone-treatment [37], chemotherapeutic agents [23,38] or heat shock [39] induced apoptosis by markedly decreasing the expression of clusterin/ApoJ, in a dose-and time-dependent manner [23]. The downregulation of clusterin/apoJ in keratinocytes undergoing ropivacaine-mediated apoptosis is in agreement with previous studies [40].…”
Section: Discussionsupporting
confidence: 89%
“…Depending on the cell metabolic contest and stimulus, clusterin would have both pro-and anti-apoptotic properties, probably because of different protein products (clusterin isoforms) coded by the same gene. In this view, a secreted form of clusterin would act as a cytoprotective protein (31)(32)(33), also acting as an extracellular chaperone-inducing phagocytosis (34,35), although a nuclear form, possibly starting from a second in-frame ATG, was suggested to be a cell death protein (18,20). As a consequence of different pro-apoptotic stimuli (and/or through different mechanisms not elucidated completely yet), the biosynthesis of a not-secreted, truncated form of clusterin would take place in the cell, and its accumulation would commit cells to apoptotic death.…”
Section: Discussionmentioning
confidence: 99%
“…sCLU is known as an extracellular secreted glycoprotein in the mature form that is upregulated in a variety of cell lines in response to stress and enhances cell survival (11). However, a number of studies have demonstrated that sCLU can also act as a cytoprotective protein (12)(13)(14). nCLU with nuclear localization has recently been described to be associated with cell death (15).…”
Section: Introductionmentioning
confidence: 99%